Analytical Application of the Pigment Isolated from Iraqi Red Radish Peels (Raphanus Sativus L) - AI-Salihi, N.J; A I-Hassan, I. A.A; Sebah, F. S (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The anthocyanin navonoid pigment isolated from lrdqi red radish peels (Raphanus Sativus L) was used as an acid - base indicator with a pk equal 7.0 and pH equal (6-8). TI1e acidic water extract was successfully used instead of conventional litmus papers.